PENINGKATAN HASIL BELAJAR MATEMATIKA OPERASI HITUNG PECAHAN MELALUI MODEL PEMBELAJARAN NHT (NUMBERED HEAD TOGETHER) DI KELAS V SDS JAKARTA ISLAMIC SCHOOL - WIBISANA, BAMBANG TRESNA; U.S, SUPARDI (KNOWLEDGE: Jurnal Inovasi Hasil Penelitian dan Pengembangan, 2024)
This study aims to improve the achievement of learning outcomes through a cooperative model with the Numbered Head Together (NHT) type for fifth grade students of SDS Jakarta Islamic School on the material of fraction calculation operations through the application of the NHT type cooperative learning model. The research was conducted at SDS Jakarta Islamic School, Cipinang Melayu Village, East Jakarta District. Geographically, this school has a strategic location and is easily accessible by parents because of its strategic location in front of Kalimalang and Jatiwaringin highways with 16 male students. The data of this study were obtained from the learning outcome test to see the success of students after the application of the NHT type cooperative learning model. Observation sheets for teachers and students were used to see the condition of the implementation of the action. The procedure in this study consisted of: planning, action implementation, observation and evaluation, and reflection. This type of research is quantitative data and qualitative data. Quantitative data was obtained from math learning outcomes based on the evaluation of each cycle and qualitative data was taken from observation. The data sources of this research are teachers and students. This type of research is Classroom Action Research (PTK). The results showed an increase in learning outcomes, teacher and student activities through the application of the NHT type cooperative learning model. This can be seen from the percentage of each cycle. Student learning outcomes increased from the increase in learning outcomes in cycle I, the percentage of student learning completeness reached 75% with an average of 76.88. In cycle II, the percentage of student learning completeness reached 100% with an average score of 89.7. The increase in student learning outcomes from cycle I to cycle II was 25%. ABSTRAKPenelitian ini bertujuan untuk meningkatkan prestasi hasil belajar melalui model kooperatif dengan tipe Numbered Head Together (NHT) pada siswa kelas V SDS Jakarta Islamic School pada materi operasi hitung pecahan melalui penerapan model pembelajaran kooperatif tipe NHT. Penelitian dilaksanakan di SDS Jakarta Islamic School, Kelurahan Cipinang Melayu, Kecamatan Jakarta Timur. Data penelitian ini diperoleh dari tes hasil 16 siswa laki-laki. belajar untuk melihat keberhasilan siswa setelah penerapan model pembelajaran kooperatif tipe NHT. Lembar observasi untuk guru dan siswa digunakan untuk melihat kondisi pelaksanaan tindakan. Prosedur dalam penelitian ini terdiri dari: perencanaan,pelaksanaan tindakan, observasi dan evaluasi, serta refleksi. Jenis penelitian iniadalah data kuantitatif dan data kualitatif. Data kuantitatif diperoleh dari hasil belajar matematika berdasarkan evaluasi setiap siklus dan data kualitatif diambil dari hasil observasi. Sumber data penelitian ini adalah guru dan siswa. Jenis penelitian ini adalah Penelitian Tindakan Kelas (PTK). Hasil penelitian menunjukkan adanya peningkatan hasil belajar, aktivitas guru dan siswa melalui penerapan model pembelajaran kooperatif tipe NHT. Hal ini dapat dilihat dari dari persentase setiap siklus. Hasil belajar siswa meningkat dari peningkatan hasil belajar siklus I presentase ketuntasan belajar siswa mencapai 75% dengan rata-rata 76,88. Pada siklus II presentase ketuntasan belajar siswa mencapai 100% dengan nilai rata-rata 89,7. Peningkatan hasil belajar siswa dari siklus I ke siklus II sebesar 25%.